(untitled) (Academicia Globe: Inderscience Research, 2021)
Pastures are the main source of fodder for livestock breeding and can be used all year round. Vegetation of pastures is the cheapest source of fodder. The productivity of desert pastures is directly related to weather conditions, so it changes dramatically with the years and seasons. In years with high precipitation, pasture yields double, and dry years reduce pasture yields by 0.5-1.0 c/ha. Long-term observations show that for every ten years the yield is repeated in this form - 3 years of good, 4 years of average and 3 years of low yield.